Association between prenatal care and small for gestational age birth: an ecological study in Quebec, Canada - N. Savard; P. Levallois; LP. Rivest; S. Gingras (Health Promotion and Chronic Disease Prevention in Canada, 2016)
Background: In Quebec, women living on low income receive a number of additional prenatal care visits, determined by their area of residence, of both multi-component and food supplementation programs. We investigated whether increasing the number of visits reduces the odds of the main outcome of small for gestational age (SGA) birth (weight o 10th percentile on the Canadian scale). Methods: In this ecological study, births were identified from Quebec’s registry of demographic events between 2006 and 2008 (n ¼ 156 404; 134 areas). Individual characteristics were extracted from the registry, and portraits of the general population were deduced from data on multi-component and food supplement interventions, the Canadian census and the Canadian Community Health Survey. Mothers without a high school diploma were eligible for the programs. Multilevel logistic regression models were fitted using generalized estimating equations to account for the correlation between individuals on the same territory. Potential confounders included sedentary behaviour and cigarette smoking. The odds ratios (ORs) were adjusted for mother’s age, marital status, parity, program coverage and mean income in the area. Results: Mothers eligible for the programs remain at a higher odds of SGA than noneligible mothers (OR ¼ 1.40; 95% confidence interval [CI]: 1.30–1.51). Further, areas that provide more visits to eligible mothers (4–6 food supplementation visits) seem more successful at reducing the frequency of SGA birth than those that provide 1–2 or 3 visits (OR ¼ 0.86; 95% CI: 0.75–0.99). Conclusions: Further studies that validate whether an increase in the number of prenatal care interventions reduces the odds of SGA birth in different populations and evaluate other potential benefits for the children should be done.